Conservation of in vitro shoots of Rhodiola sachalinensis by slow growth and its DNA content analysis - LIU Jian-feng; YAN Xiu-feng; CHENG Yun-qing; ZHOU Xiao-mei; ZHANG Xiao-yan (浙江大学学报. 农业与生命科学版)
In order to establish conservation system of in vitro shoots of Rhodiola sachalinensis by slow growth, studies on conservation of in vitro shoots of two resources by slow growth under low temperature, week illumination and mannitol of different concentration were carried out, and DNA contents of those recovered plantlets were analyzed. The results indicated that more than 85% of in vitro shoots conserved on 1/2MS supplemented with 20 g·L-1 sucrose, 7 g·L-1 agar and 10 g·L-1 mannitol maintained viability after 18 months under (6±1)℃ and 600 lx conditions. Both nuclear DNA contents maintained as normal. Thus, it was suggested these procedures would be effective and viable to conserve Rhodiola sachalinensis by slow growth as above.